2016
DOI: 10.1002/ab.21653
|View full text |Cite
|
Sign up to set email alerts
|

Defending victimized peers: Opposing the bully, supporting the victim, or both?

Abstract: To reduce bullying, more knowledge on children defending their victimized peers is critical. In previous work, predominantly cross-sectional in nature, defending has typically been operationalized as one single, broad construct. However, there are good reasons to assume that attacking the bully (bully oriented defending) and comforting the victim (victim-oriented defending) are relatively independent constructs, with potentially different correlates. This longitudinal study in the Netherlands (N = 394; M = 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
91
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 47 publications
13
91
2
4
Order By: Relevance
“…Finally, it must be noted that Reijntjes et al () found that direct defending had positive ties with bullying and was strongly present in peer‐classified probullying adolescents. Similarly, Huitsing et al () suggested that adolescents in probullying cliques use peer defending to help each other.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Finally, it must be noted that Reijntjes et al () found that direct defending had positive ties with bullying and was strongly present in peer‐classified probullying adolescents. Similarly, Huitsing et al () suggested that adolescents in probullying cliques use peer defending to help each other.…”
Section: Introductionmentioning
confidence: 97%
“…Reijntjes et al () were the first to explicitly investigate the potential heterogeneity of adolescents’ peer defending. In their study, three defender groups with distinct status patterns surfaced: (a) indirect defenders, who were high in social preference but low in popularity, (b) direct defenders, who were low in social preference but high in popularity, and (c) hybrid defenders, who were high in both social preference and popularity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations